Interstitial lung disease induced by docetaxel and ramucirumab chemotherapy after nivolumab treatment - Okeya, Komugi (Respirol Case Rep, 2020)
Three men (aged 64, 65, and 67 years) with advanced lung cancer who had been treated with nivolumab developed interstitial lung disease (ILD) during chemotherapy with docetaxel and ramucirumab. The treatment was clinically effective; however, the patients experienced immune‐related adverse effects due to nivolumab therapy: two patients developed ILD and the third developed psoriasis. Because the patients showed progression, docetaxel and ramucirumab chemotherapy was administered. Although two patients showed a clinical response, all patients developed grade 3 ILD during therapy. Furthermore, the patients developed respiratory failure and needed corticosteroid therapy. Although their condition improved owing to the therapy, the patients could not receive additional cancer treatment and died of cancer. On the basis of the results obtained, we speculated that although the regimen of docetaxel and ramucirumab after nivolumab therapy might be effective against non‐small cell lung cancer, it might increase the risk for ILD in some patients.